Septum primum malposition defect and inferior sinus venosus defect: a rare association. (2nd October 2014) - Prasad, Deepa; Snyder, Christopher; Ashwath, Ravi
Abstract We present a case of a 2-year-old girl who presented with respiratory distress and umbilical abscess, and was found to have an inferior sinus venosus defect, malposition of the atrial septum primum, absent septum secundum, and anomalous drainage of the right upper and lower pulmonary veins to the right atrium.